Gas turbine minimum environmental load extension with compressed air extraction for storage. (5th November 2020) - Abudu, Kamal; Igie, Uyioghosa; Minervino, Orlando; Hamilton, Richard
Highlights: Minimum environmental load extension of 34% was achieved through airflow extraction. Maintaining the maximum combustor temperature at low-loads is crucial to control CO. Back stage flow extraction pushes neighbouring stages towards choke condition. Flow extraction after VIGV closure further reduces the power and thermal efficiency. Abstract: The fact that most renewable forms of energy are not available on-demand and are typically characterised by intermittent generation currently makes gas turbine engines an important source of back-up power. This study focuses on one of the capabilities that ensure that gas turbines are more flexible on the electric power grid. The capability here is the minimum environmental load that makes it possible to keep a gas turbine engine on the grid without a shut-down, to offer grid stability, adding inertia to the grid in periods when there is no demand for peak power from the engine. It is then desirable to operate the engine at the lowest possible load, without infringing on carbon monoxide emissions that becomes dominant. This paper demonstrates this potential through the extraction of the pressurised air from the back end of the compressor into an assumed energy storage system. The simulation of the engine performance using an in-house tool shows the additional reduction of the power output when the maximum closing of variable inlet guide vane is complemented with air extractions. However, the identified key strategy for achieving a lower environmental load (with same carbon monoxide emission limit) is to always maintain the design flame temperature. This is contrary to the conventional approach that involves a decrease in such temperatures. Here, a 34% reduction in load was achieved with 24% of flow extraction. This is shown to vary with ambient temperatures, in favour of lower temperatures when the combustor inlet pressures are higher. The emission models applied were based on empirical correlations and shows that higher combustor inlet pressures, high but constant flame temperatures with core flow reduction is crucial to obtaining a low environmentally compliant load. The compressor analysis shows that choking is a noticeable effect at a higher rate of extractions; this is found to occur at the stages closest to the extraction location.